2022
DOI: 10.3390/foods11071001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects against Alpha-Amylase of an Enriched Polyphenol Extract from Pericarp of Mangosteen (Garcinia mangostana)

Abstract: The pericarp of mangosteen, a by-product of the mangosteen, is rich in polyphenols. In this study, an efficient and environmentally friendly method for preparative enrichment of polyphenols from mangosteen pericarp (MPPs) was developed, and the inhibitory effects on starch digestion were also evaluated. It was found that the optimal extract method of MPPs was at a solid to solvent ratio of 1:50 g/mL, pH of 2, and at 80 °C for 2 h. The IC50 of MPPs for α-amylase was 0.28 mg/mL. Based on the fluorescence quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Te study by Li et al in 2022 showed 20 and 40 mg/kg of oral pericarp extracts of G. mangostana to HFD-induced Sprague-Dawley (SD) rats an inhibitory efect on α-amylase activity and signifcantly reduced post-prandial blood glucose [48].…”
Section: Protective Efects Of Mangosteenmentioning
confidence: 99%
“…Te study by Li et al in 2022 showed 20 and 40 mg/kg of oral pericarp extracts of G. mangostana to HFD-induced Sprague-Dawley (SD) rats an inhibitory efect on α-amylase activity and signifcantly reduced post-prandial blood glucose [48].…”
Section: Protective Efects Of Mangosteenmentioning
confidence: 99%
“…Tropical trees of the Garcinia genus are mainly distributed in Southeast Asia, India, Africa, and Brazil, and many of them have medicinal and culinary uses Garcinia plants are an important source of polyphenols, including flavonoids, xanthones, and phloroglucinols. In particular, caged xanthones with a partially dearomatized prenylated polyphenol core have attracted considerable attention owing to their complex carbon skeleton and potential antitumor activity . The most representative caged xanthone, gambogic acid, entered clinical trials to treat colon, non-small cell lung, and renal cancers in China .…”
mentioning
confidence: 99%